Variability of Indonesian Throughflow and Borneo Runoff During the Last 14 kyr. (26th October 2017) - Hendrizan, Marfasran; Kuhnt, Wolfgang; Holbourn, Ann
Abstract: We present a high‐resolution (~20 to 100 years temporal resolution) reconstruction of hydrological changes in the Makassar Strait over the last 14 kyr from Core SO217‐18517 retrieved off the Mahakam Delta (1°32.198′S, 117°33.756′E; 698 m water depth) during the SO217 Makassar‐Java Cruise. Sea surface temperatures, based on Mg/Ca of Globigerinoides ruber and alkenone U K′ 37, and seawater δ 18 O reconstructions, based on G. ruber δ 18 O and Mg/Ca, in combination with sortable silt grain size measurements and X‐ray fluorescence (XRF) core scanner derived elemental data provide evidence for increased precipitation during the Bølling‐Allerød (BA) and early Holocene and for warmer and more saline surface waters and a decrease in the intensity of the Indonesian Throughflow (ITF) during the Younger Dryas (YD). XRF derived Log (Zr/Rb) records, sortable silt data and increased sedimentation rates indicate decreased winnowing, interpreted as a slowdown of the ITF thermocline flow during the YD. We attribute this decline in ITF intensity to slowdown of the Atlantic meridional overturning circulation during the YD. We suggest that changes in Makassar Strait surface hydrology during this interval of Northern Hemisphere cooling and Southern Hemisphere warming were related to a southward displacement of the Intertropical Convergence Zone. Key Points: Multiproxy records of Makassar Strait hydrology over the past 14 ka Slowdown of Indonesian Throughflow and drying of Borneo during Younger Dryas Latitudinal displacement of ITCZ controlled Makassar Strait surface hydrology